INTERIOR DESIGNING OF SEMARANG CONVENTION CENTER UNDER THE THEME OF ASEM ARANG-ARANG - Devi Wijiyanto; Sumarno Sumarno (Institut Seni Indonesia Surakarta, 2020)
Semarang, as the capital of Central Java Province, with its high economic and tourism growth, needs to be supported with adequate facilities and infrastructure. The purpose of designing is to fulfill exhibition and meeting facilities in the city of Semarang, Indonesia. The design method adopts the stages of the Kurtz programming design process. The theme of asem arang-arang is a local character in Semarang, Indonesia, with a post-modern style. The interior design drawings of Semarang Convention Center include the main lobby (exhibition hall area), side lobby (convention hall area), convention hall, exhibition hall, meeting/conferences room, and cafeteria. The benefit of the design is as a reference for the Semarang city government and the parties involved in developing infrastructure and facilities in Semarang.